Potencialidade hídrica do sistema aquífero serra geral da bacia hidrográfica do Rio da Várzea - Nery, Bianca Johann (2023)
The Várzea Watershed (BHRV) has represents an important contribution of water discharge to the Uruguay River. The watershed is overlying the basalts of the Serra Geral Formation, which in turn, constitute the Serra Geral Aquifer System. Analyzing the quality of the Basin's groundwater, as well as mapping the areas according to the potential for groundwater production, allows subsidizing public policies aimed at meeting Goal 6 of Sustainable Development, proposed by the UN's 2030 Agenda. Thus, this study aimed to evaluate the productivity of wells, through their specific capacity, relating it to the geological-structural elements of the Serra Geral Formation, such as: the type of rock, the type of aquifer, the thickness of the soil, the direction and density of the lineaments, and the intersection between them. Also, the hydrochemical characteristics of groundwater in the BHRV were evaluated, as well as the quality of these waters for human consumption. It is observed that the wells under the Fácies Paranapanema and under the Serra Geral I Aquifer System (SASG I) have a higher specific capacity in addition to higher productivity when installed on soils with intermediate thickness. The SE-SSE and E-ESE lineament directions showed a directly proportional correlation between the highest median specific capacity of wells and lineament density per area. Significance was not verified in the lineament intersection density analysis, with the exception of areas with higher intersection density (>0.1/km2), which showed greater specific capacity. The directions of lineaments that presented nearby wells (less than 1 km away) with higher median specific capacity were: ESE-SE and NE-ENE. The study also showed that the waters are predominantly sodium bicarbonate and weakly sodium, with low salinity. Of 151 wells analyzed, 42% presented parameters with values above the VMP for human consumption, such as pH, which in 24.67% of the wells presented values greater than 9 (84.67% of the groundwater in the basin is more basic than acidic). The application of this study seeks to provide subsidies for the drilling of wells in potentially productive zones from a qualiquantitative point of view in the SASG fractured aquifer.